2018
DOI: 10.1039/c7ta11346c
|View full text |Cite
|
Sign up to set email alerts
|

Extracting maximum capacity from Ni-rich Li[Ni0.95Co0.025Mn0.025]O2cathodes for high-energy-density lithium-ion batteries

Abstract: Capacity degradation of highly Ni-enriched NCM cathodes is aggravated by the formation of the H3 phase in the delithiated state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
112
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(125 citation statements)
references
References 24 publications
12
112
1
Order By: Relevance
“…[31] attributed these features to Li vacancyo rdering in the Li planes, andi n fact, Peres et al [32] verified experimentally such ordering in monoclinic LNO using electron diffraction measurements. [4,33] However,i ti sa lso evident from the data shown in Figure 4a that the H1-H1' peak vanishes during discharge when the C-rate is increased (here, from the 4th cycle onward). [1,2,5,6,8,19] Interestingly, this peak has not been observed for Ni-rich NCMs, even for compositions close to that of LNO (!…”
Section: Neutrondiffractionmentioning
confidence: 89%
See 2 more Smart Citations
“…[31] attributed these features to Li vacancyo rdering in the Li planes, andi n fact, Peres et al [32] verified experimentally such ordering in monoclinic LNO using electron diffraction measurements. [4,33] However,i ti sa lso evident from the data shown in Figure 4a that the H1-H1' peak vanishes during discharge when the C-rate is increased (here, from the 4th cycle onward). [1,2,5,6,8,19] Interestingly, this peak has not been observed for Ni-rich NCMs, even for compositions close to that of LNO (!…”
Section: Neutrondiffractionmentioning
confidence: 89%
“…In addition to the peaks that are known to be related to the first-order H1-M, M-H2, and H2-H3 transformations, [19] the presence of some other peaks of lower intensity can also be noticed. [33] In recent years, it has been shown that reordering of Li ions, without affecting the hexagonal symmetry,c an occur for x(Li)a pproxi- Figure 3. [31] attributed these features to Li vacancyo rdering in the Li planes, andi n fact, Peres et al [32] verified experimentally such ordering in monoclinic LNO using electron diffraction measurements.…”
Section: Neutrondiffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial cycle discharge capacities of the M0.01−NCA and M0.02−NCA are 183.6 and 175 mAh g −1 following by discharge capacities of 150.9 and 133.3 mAh g −1 after 200 cycles, showing higher capacity retention of 82.2 and 76.2%, respectively. While for the higher voltage cutoff of 4.5 V, the pristine NCA, M0.01‐the pristine NCA, M0.01−NCA, and M0.02−NCA samples show capacity retention of 77.7, 86 and 83% after 100 cycles at 1 C. To illustrate the improvement of cycling performance, Figure (c) shows the cycling performance diagram compared with some of the latest reported works at 4.3 V cut‐off voltage after 100 cycles, and all the involved nickel‐rich cathode materials have similar stoichiometric ratios . It is noted that our work is comparable with them, but cycling performance needs to be improved regarding the discharge capacity.…”
Section: Resultsmentioning
confidence: 93%
“…Figure 6 Figure 6(c) shows the cycling performance diagram compared with some of the latest reported works at 4.3 V cut-off voltage after 100 cycles, and all the involved nickel-rich cathode materials have similar stoichiometric ratios. [34][35][36][37][38] It is noted that our work is comparable with them, but cycling performance needs to be improved regarding the discharge capacity. Specially, the charge and discharge curves of the 1st, 25th, 50th, 100th, 150th, 200th cycle between 2.5 and 4.3 V for the pristine and M0.01À NCA are shown in Figure S4.…”
Section: Full Papermentioning
confidence: 87%